Pelaksanaan Eksekusi Putusan Serta Merta - Anisa Astri Nuraheni; Harjono, S.H., M.H - (Sebelas Maret University, 2017)
This study describes and examines the procedure of uitvoerbarr bij voorrad execution. The obstacles that must be faced in uitvoerbarr bij voorrad on the decision number 08 / Pdt.G / PN.Pwr. This research is a descriptive of empirical legal research. The sources of data were collected from primary data source and secondary data source. The data collection through interviews and literature study. The technique of analyzing data is qualitative technique with interactive models. The results of the research showed that the Mr. GWH as a Plantiff proposed claim to Mr.KTB as a Defendant to Purworejo District Court. The object dispute as the land and buildings which located in Purworejo Village, Subdistrict of Purwrejo, Purworejo District, listed by name Mr. GLG an area of 374 m2. One of the injunctions stated that this decision can be implemented first, howefer there will be a common legal remedy as wel as extraordinary legal remedy. The procedures for uitvoerbarr bij voorrad execution is the consent of the Chairman of the High Court to carry out the uitvoerbarr bij voorrad execution, the Determination of the Chairman of the District Court to do aanmaning, admonition/ aanmaning, the promulgation of the execution order by the Chairman of the District Court, then the execution can be carried out with attended by two witnesses. In carrying out the uitvoerbarr bij voorrad execution of number 08 / Pdt.G / PN.Pwr, there were several obstacles, namely: the Respondent objected to the execution of the object dispute. There was a tension between the Registrar and the security services with the Respondent of execution, The Respondent of execution was not willing to leave the land with the house dispute. Keywords: Execution, uitvoerbarr bij voorrad